2018
DOI: 10.1002/jcb.27699
|View full text |Cite
|
Sign up to set email alerts
|

The AP2M1 gene expression is a promising biomarker for predicting survival of patients with hepatocellular carcinoma

Abstract: There is a growing need for the discovery of new prognostic factors for cases where the scoring and staging system of hepatocellular carcinoma (HCC) does not result in a clear definition. We analyzed whether AP-2 complex subunit mu (AP2M1) expression could be a new prognostic marker for HCC based on the roles of AP2M1 in influencing hepatocyte growth factor (HGF) promoter regulation and hepatitis C virus (HCV) assembly. Patient data were extracted from cohorts of the Gene Expression Omnibus (GSE10186), Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 22 publications
4
53
0
Order By: Relevance
“…The high expression level of AP2M1 showed poor prognostic of HCC patients especially with HCV infection and/or alcohol intake. 7 The results in our study suggested that CFHR3, SAC3D1, and AP2M1 had good predictive value for HCC.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The high expression level of AP2M1 showed poor prognostic of HCC patients especially with HCV infection and/or alcohol intake. 7 The results in our study suggested that CFHR3, SAC3D1, and AP2M1 had good predictive value for HCC.…”
Section: Discussionsupporting
confidence: 55%
“…Another example is AP2M1 (AP‐2 complex subunit mu) which is a transcription factor regulating hepatocyte growth factor promoter and hepatitis C virus (HCV) assembly. The high expression level of AP2M1 showed poor prognostic of HCC patients especially with HCV infection and/or alcohol intake . The results in our study suggested that CFHR3, SAC3D1, and AP2M1 had good predictive value for HCC.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Furthermore, we used 2 methods to evaluate biomarker performance: (1) Uno's C-index in the time-dependent area under the curve (AUC) analysis and (2) AUC values in receiver operating characteristic (ROC) curves at the 3-year mark as we described previously [25,26]. These values were calculated using the R packages "survival" and "survAUC".…”
Section: Discussionmentioning
confidence: 99%